Perfil gustativo de idosas ativas: frequência de hipogeusia e fatores associados - Medina, Vanessa Bischoff (2016)
The reduction in taste perception related to age may be related to life quality and life style, health conditions and dietary choices made by elderly people. Objective: Identify the flavor profile of active elderly women, frequency of hypogeusia and associate this condition with habits and life quality and nutritional status. Methodology: It was analyzed elderly women who were part of senior citizens’ organization, being able to cognition according to the Mini Mental State Examination (MMSE), free of injuries or wounds or mouth bleeding, without recent treatment of chemotherapy or radiotherapy, without hospitalization in the period. These elderly women were investigated through an interview, which contained socio demographic variables, life habits and health. Using their weight and height, it was calculated the Body Mass Index (BMI), analysis of the dietary quality occurred by the test “How are your eating habits?”, to analyze the palate were used “strips of taste” made of filter paper soaked in four different concentrations of the sweet, salty, bitter and acid flavors. Descriptive analysis demonstrated the total number of subjects and the respective percentage in each category of variables, the Chi-Square test was used to compare the groups with and without hypogeusia, average comparison was assessed by the T-Student Test and the models of Poisson Regression were built to evaluate these associations. Results: In the total, composed the sample, 64 elderly women, with an average age of 69,8±7,3 years old, 64,1% earned less than R$ 2.500,00, had an education equal to or higher than 5 years of study (81,2%), most of the elderly women have two or less comorbidity (78,1%) and they use regularly up to 3 medicines (76,6%); high predominance of using dental prosthesis (85,9%), benefic self-evaluation of life quality 84,4% and health 54,7%; predominance of overweight and obesity (56,2%) and the evaluation of dietary quality resulted as satisfactory. The mean in the total score of the flavor evaluation was 11,9±2, the percentile 10th showed correct identification up to 7 flavors, 10,09% of the elderly women evaluated showed hypogeusia. Sweet and bitter flavors showed higher average of correct answers and acid flavor (<0,001) and salty flavor (<0,001) showed greater statistic differences in the group with or without hypogeusia, this condition was not statistically associated to socio demographic data, style, life quality and nutritional status. Conclusion: It was found a small percentage of hypogeusia in the sample; this condition was not statistically related to the facts analyzed. Salty and acid flavors showed the greater differences for detection and correct answers between the subjects with or without hypogeusia.